2007
DOI: 10.1038/sj.cgt.7701079
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of NK4 to multiple lung tumors by bone marrow-derived mesenchymal stem cells

Abstract: Most advanced solid tumors metastasize to different organs. However, no gene therapy effective for multiple tumors has yet been developed. Since a unique characteristic of bone marrow-derived mesenchymal stem cells (MSCs) is that they migrate to tumor tissues, we wanted to determine whether MSCs could serve as a vehicle of gene therapy for targeting multiple tumors. First, we confirmed that mouse MSCs preferentially migrate to multiple tumors of the lung in the Colon-26 (C-26) lung metastasis model. Next, MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 38 publications
1
85
0
1
Order By: Relevance
“…Thus, application of MSC has no apparent adverse side effects, since the mice in our experiments looked healthy after administration of MSC, and another report demonstrated that MSC overexpressing the adenoviral-transduced NK4 gene did not lead to enhanced liver enzymes in serum. 35 Therefore, selective engraftment of MSC expressing an antitumor agent in the tumor tissues should be sufficiently therapeutically advantageous to warrant further clinical trials. However, practical realization of efficient gene transfer by MSC vehicles has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, application of MSC has no apparent adverse side effects, since the mice in our experiments looked healthy after administration of MSC, and another report demonstrated that MSC overexpressing the adenoviral-transduced NK4 gene did not lead to enhanced liver enzymes in serum. 35 Therefore, selective engraftment of MSC expressing an antitumor agent in the tumor tissues should be sufficiently therapeutically advantageous to warrant further clinical trials. However, practical realization of efficient gene transfer by MSC vehicles has been limited.…”
Section: Discussionmentioning
confidence: 99%
“…43 Improved transduction of adenoviral vectors to MSC has been shown using modification to include the RGD (Arg-Gly-Asp) motif on the penton fiber. Adopting this strategy, Kanehira et al 44 transduced NK4, an antagonist of hepatocyte growth factor and significantly prolonged the survival of mice bearing colon-26 cell line xenograft in lungs by inhibiting angiogenesis and lymphangiogenesis and inducing apoptosis of tumor cells. Antitumor activity of retrovirus vector transduced MSC, producing IL-12, has been tested in a mouse melanoma model.…”
Section: Lung Metastasismentioning
confidence: 99%
“…Instead, the most exciting and clinically relevant finding is that MSCs possess unique tumor-trophic, drug-resistant and migratory properties and overexpress efflux transporters such as P-glycoproteins [125]. These features have founded the rationale to develop MSCs as vehicles to deliver specific anti-angiogenic and anti-tumor agents [127,128]. These genetically engineered MSCs can successfully deliver an antagonist of the hepatocyte growth factor, the TNF-related apoptosis-inducing ligand (TRAIL) and IFN-a with potent anti-tumor effects both in vitro and in vivo [128][129][130].…”
Section: Potential Targetsmentioning
confidence: 99%
“…These features have founded the rationale to develop MSCs as vehicles to deliver specific anti-angiogenic and anti-tumor agents [127,128]. These genetically engineered MSCs can successfully deliver an antagonist of the hepatocyte growth factor, the TNF-related apoptosis-inducing ligand (TRAIL) and IFN-a with potent anti-tumor effects both in vitro and in vivo [128][129][130]. However, concerns about their biosafety and feasibility has led to the development of MSCs containing drug loaded nanoparticles [131] whose therapeutic effectiveness depends on the specificity of their migration and engraftment and is enhanced by local radiotherapy [132].…”
Section: Potential Targetsmentioning
confidence: 99%